THE RELATIONSHIP BETWEEN PATIENT MOTIVATION AND SELF-CARE IN PATIENTS WITH SELF-CARE DEFICIT IN BALEE MAWAR WARD, ACEH MENTAL HOSPITAL - Popy Citra Sari Morian; Rhieaqi Chintya Fonna; Maghfiratul Ulfa; Ayuni Atiqah; Siti Nur Nazirah; Maulida Maulida (Universitas Bina Bangsa Getsempena, 2024)
Self-care deficit commonly occurs in individuals with mental disorders due to impairments in thought processes, motivation, and functional ability. This study aimed to analyze the relationship between patient motivation and self-care among individuals with self-care deficit in Balee Mawar Ward, Aceh Mental Hospital, in 2023. A quantitative correlational design with a cross-sectional approach was employed. A total sampling technique was used involving 35 respondents. Motivation and self-care were measured using validated Guttman-scale observation instruments. Results revealed that 60.0% of patients had high motivation, whereas 51.4% demonstrated poor self-care. Chi-square analysis indicated a significant relationship between motivation and self-care (p = 0.000). Positive reinforcement through praise and rewards contributed to improved cleanliness and independence. These findings highlight the importance of motivation-focused nursing interventions to enhance self-care among psychiatric patients